Extreme Optics: Inverse Design and Experimental Realizations of Ultra-Large-Area Complex Meta-Optics - Pestourie, R.; Li, Z.; Bayati, E.; Park, J-S; Huang, Y-W; Colburn, S.; Lin, Z.; Majumdar, A.; Capasso, F.; Johnson, S. G. (2021 FIFTEENTH INTERNATIONAL CONGRESS ON ARTIFICIAL MATERIALS FOR NOVEL WAVE PHENOMENA (METAMATERIALS), 2021)
We present a design framework for metasurface that uses a hybrid approximate solver for Maxwell's equations, which separates the comptutation for the metasurface's nano-scale and macro-scale, and thus makes large-diameter inverse design tractable on a laptop. We further demonstrate experimental realizations of ultra-large-area metasurfaces designed using this framework: (1) a lens with extended depth of field with a millimeter diameter, and (2) polychromatic lenses with diameters of up to 1 cm.